Pengaruh Karakteristik Entrepreneur dan Efikasi Diri Terhadap Kesiapan Kerja Mahasiswa - Ainaiya Alfatihah; Elvi Rahmi (Universitas Negeri Padang, 2022)
The objectives of this study are to determine the effect of entrepreneurial characteristics on work readiness of students of the Faculty of Economics, Padang State University, the impact of self-efficacy on work readiness of students of the Faculty of Economics, State University of Padang, and the effect of entrepreneurial characteristics and self-efficacy on work readiness of students of the Faculty of Economics, State University of Padang. The method used in this research is quantitative with the post facto research type. The population in this study were undergraduate students of the economics faculty of the Padang State University in 2017-2019 as many as 1708 samples. The study was measured using the Slovin formula, while the sampling technique was carried out by Proportional Stratified Random Sampling and obtained a total sample of 324 students. The analysis technique used is descriptive analysis and inductive analysis. The hypothesis testing used is the F test and T-test using the SPSS 20 application. The results revealed that (1) entrepreneurial characteristics affect student work readiness, (2) self-efficacy affects student work readiness, (3) entrepreneurial characteristics and self-efficacy affect student work readiness. Based on this research, the writer suggests students maximize their entrepreneurial and self-efficacy characteristics because they are two crucial assets in forming readiness to face the world of work.Keywords Entrepreneurial Characteristics, Self-efficacy, Work Readiness